الإتصال المؤسساتي في القطاع الجمعوي في الجزائر - بروك ياسين (My University, 2022)
Abstract: This study aimed at identifying the reality of the practice of corporate communication in the associative sector in Algeria, through an attempt to understand, extrapolate and interpret its exploratory and explanatory descriptive aspects, starting from conducting a comprehensive survey on Algerian national associations active in Souk Ahras, represented by fourty five (45) research leaders,( presidents of associations along with people in charge of communication), using a veriety of data collection tools: qualitative (participatory observation, exploratory interviews, qualitative level in content analysis) as well as quantitative (quantitative level in content analysis), and a standardized interview questionnairewithin the framework of the mixed methodological approach in order to achieve the objectives of the study in all its stages, using the appropriate social survey method for this type of descriptive studies. Accordingly, this study is based in its approach to reality on the communicative approaches of three main theoretical approaches (social marketing, management by objectives, and situational perspectives) which employs them together to approach the subject of the study according to an integrated synthesis of knowledge and theory in the form of an analytical model designed by the researcher through the modeling process that goes in line with the ideas and statements of the systemic paradigm that views the institution (the association) as a system open to its internal and external as well as general environment in which the components and parts seek to achieve the common goal of the general coordination within the framework of an interactive process by activating and supporting communication efforts to achieve and mantain balance. This study reached a set of results: First –Regarding corporate communication processes of the associations studied: The lack of the person in charge of communication for a large number of active national associations in the field of the study, and the absence of his primary role in a number of others, assigning him just to specific and limited tasks, Also, these associations did not seek much to develop their relations with the press in light of the media institutions’ lack of interest in publishing the news, valuesand objectives of these associations. As for assessing the level of characteristics of the rest of the elements of the corporate communication process for these associations active in the field of study (message, props, means, techniques and mechanisms, the target audience...etc.), is generally good. However, it varies from one association to another in terms of: selection, planning, implementation, evaluation, andstraightening in accordance with the human and material capabilities of the association, its basic law, its objectives, the nature of its activity, the type of programmed activity, the social attitudes and the type of social valuesintended to be marketed. Second -Concerning the objectives of corporate communication in the associative sector: The national associations active in the field of study seek to achieve the most important goals of corporate communication in the associative sector, which are: introducing the association, striving towards achieving the socially responsible association and the citizenship association, and forming a positive mental image among its internal as well as external audience using the various strategies of corporate communication within the limits of the available human and material capabilityes. However, this endeavor in light of giving priority to the interest of one audience at the expense of another - as the study found - needs to work towards intensive activation to achieve these goals in the field through improving, supporting and strengthening the programs and communication efforts of each of these associations. Third -obstacles to corporate communication in the associative sector(at the level of the associations studied): Different and numerous are the obstacles to corporate communication in the associative sector of Souk Ahras. They vary between the financial obstacles such as: the absence of headquarters for many associations, and the lack and - sometimes - the total non-existence ofresources and financial aid for the practice of associative activity, as well as organizational obstacles: mainly the weakness of the system of laws regulating the activities of associations in many aspects, not to mention the lack of specialists in communication, and the multiplicity of tasks which sometimes causes an organizational defect .In addition to the environmental obstacles, namingly the inadequacy of the majority of the social headquarters of these associations to practice various associative activities: preparation, coordination, implementation, follow-up, evaluation and straightening,not to mention the psychological obstacles: the withdrawal of citizens from the field of associative activity, and the lack of a culture of associative and voluntary work, which led the leaders of some associations to think about dissolving their activities. --------------------------------------------------------------- ملخَص الدِّراسة: هدفت هذه الدِّراسة للتَّعرُّف على واقع ممارسة الاِتِّصال المؤسَّساتي في القطاع الجمعوي في الجزائر، من خلال محاولة فهم واِستقراء وتأويل جوانبه الاِستكشافيَّة، واِستنباط وتفسير جوانبه الوصفيَّة التَّفسيريَّة اِنطلاقًا من إجراء دراسة مسحيَّة شاملة على الجمعيَّات الوطنيَّة النَّاشطة بولاية سوق أهراس الجزائريَّة، مُمَثَّلةً في 45 مبحوثًا من قياداتها (رؤساء الجمعيَّات، والمكلَّفون بالاِتِّصال إنْ وُجِدوا) باِستخدام مجموعة متنوِّعة من أدوات جمع البيانات: الكيفيَّة منها (الملاحظة بالمشاركة، المقابلات الاِستكشافيَّة، المُسْتَوَى الكَيْفِي في تحليل المضمون) وكذا الكميَّة (المستوى الكمِّي في تحليل المضمون، اِستمارة المقابلة المُقنَّنة) في إطار المقاربة المنهجيَّة المختلطة بما يُحقِّق أهداف الدِّراسة في جميع مراحلها، مُستَخدِمين منهج المسح الاِجتماعي الملائم لهذا النَّوع من الدِّراسات الوصفيَّة، وتَسْتَنِدُ هذه الدِّراسة في مقاربتها للواقععلى المداخل الاِتِّصاليَّة لثلاث مقاربات نظريَّة أساسيَّة (التَّسويق الاِجتماعي، الإدارة بالأهداف، والموقفيَّة) وتَوظيفِها مُجتمِعةً لمُقارَبَة موضوع الدِّراسة وِفْقَ تَوْلِيفَةٍ معرفيَّة ونظريَّة مُتكامِلة في شَكْلِ نَمُوذَجٍ تَحْلِيلِيٍّ صَمَّمهُ الباحث من خلال عمليَّة النَّمْذَجَة النَّسقيَّة، بِمَا يَتَوافَقُ مع أفكار ومقولات البراديغم النَّسقي الذِّي يَنْظُرُ إلى المؤسَّسة (الجمعيَّة) بأنَّها نسق مفتوح على بيئتها الدَّاخليَّة والخارجيَّة والبيئة العامَّة، تَسْعَى فيها المكوِّنات والأجزاء لتحقيق الهدف المُشْتَرَك للنَّسقِ العامِّ في إطار عمليَّة تفاعليَّة من خلال تفعيل ودعم الجهود الاِتِّصاليَّة بِمَا يُحقِّق التَّوازن. وقد توصَّلت هذه الدِّراسة إلى مجموعة من النَّتائج نلخِّص أَبْرَزَهَا فيما يلي: أوَّلا - بخصوص خصائص سيرورة عمليَّات الاِتِّصال المؤسَّساتي للجمعيَّات محلَّ الدِّراسة: اِفتقار عدد كبير من الجمعيَّاتالوطنيَّةالنَّاشطةبميدان الدِّراسة إلى مكلَّفبالاِتِّصال بها، وتغييبدورهالأساسي في عدد آخر منها،بتكليفهبمهاممحدَّدةومحدودة، كما أنَّ هذه الجمعيَّاتلمْ تَسْعَ كثيرًالتطوير علاقاتها مع الصِّحافة في ظلِّ عدم اِهتمام المؤسَّسات الإعلاميَّة كثيرًا بنشر أخبار وقيم وأهداف هذه الجمعيَّات، أمَّا تقييم مستوى خصائص باقي عناصر عمليَّة الاِتِّصال المؤسَّساتي لهذه الجمعيَّات النَّاشطة بميدان الدِّراسة (الرِّسالة، الدعائم والوسائل والتِّقنيَّات والآليَّات، الجمهور المستهدَف...إلخ) فهو جيِّدٌ على العموم، إلاَّ أنَّه يَتبايَنُ من جمعيَّة إلى أخرى من حيث: الاِختيار، التَّخطيط، التَّنفيذ، التَّقييم، والتَّقويم، بما يتوافق مع الإمكانات البشريَّة والمادِّيَّة للجمعيَّة وقانونها الأساسي وأهدافها وطبيعة نشاطها، ونوع النَّشاط المبرمَج والمواقف الاِتِّصاليَّة، ونوع القيم المراد تسويقها اِجتماعيًّا. ثانيًّا - بخصوص أهداف الاِتِّصال المؤسَّساتي في القطاع الجمعوي بولايَّة سوق أهراس: تسعى الجمعيَّات الوطنيَّة النَّاشطة بميدان الدِّراسة إلى تحقيق أبرز أهداف الاِتِّصال المؤسَّساتي في القطاع الجمعوي، وهي: التَّعريف بالجمعيَّة، السَّعي نحو تحقيق صفة الجمعيَّة المسؤولة اِجتماعيًّا والجمعيَّة المُواطِنَة، وتَشْكِيل صورة ذهنيَّة إيجابيَّة عنها لدى جمهورها الدَّاخلي وكذا جمهورها الخارجي، باِستخدام الإستراتيجيَّات المُخْتَلِفَة للاِتِّصال المؤسَّساتي في حدود الإمكانات البَشريَّة والماديَّة المُتاحَة،غيرَ أنَّ هذا السَّعي في ظلِّ تغليب الاِهتمام بجمهور على حساب جمهور آخر -كما توَصَّلت إليه الدِّراسة- يحتاج إلى العمل نحو تفعيلٍ مكثَّف لتحقيق هذه الأهداف في الميدان من خلال تحسين ودعم وتعزيز البرامج والجهود الاِتِّصاليَّة لكلٍّ من هذه الجمعيَّات. ثالثًا - معوقات الاِتِّصال المؤسَّساتي في القطاع الجمعوي بولايَّة سوق أهراس: تَخْتَلِفُ وتَتَعدَّدُ معوقات الاِتِّصال المؤسَّساتي في القطاع الجمعوي بولايَّة سوق أهراس بين المعوقات المادِّيَّة: كغياب مقرَّات خاصَّة بالعديد من الجمعيَّات، وقلَّة و-أحيانًا- اِنعدام الموارد والمساعدات الماليَّة لممارسة النَّشاط الجمعوي، وكذا المعوقات التنظيميَّة: كضعف منظومة القوانين الخاصَّة بتنظيم نشاط الجمعيَّات في الكثير من جوانبها،ناهيك عن قلَّة المتخصِّصين في الاِتِّصال، وتعدُّد المهام، ممَّا يسبب خللاً تنظيميًّا في بعض الأحيان، إضافةً إلى المعوقات البيئيَّة: كعدم ملاءمة أغلبيَّة المقرَّات الاِجتماعيَّة لهذه الجمعيَّات لممارسةمختلفالنَّشاطاتالجمعويَّة:تحضيرًا،وتنسيقًا،وتنفيذًا،ومتابعةً،وتقييمًا،وتقويمًا، ناهيك عن المعوقات النَّفسيَّة: كاِنسحاب المواطنين من مجال النَّشاط الجمعوي، وعدم وجود ثقافة خاصَّة بالعمل الجمعوي والتَّطوُّعي، ما أدَّى بقيادات بعض الجمعيَّات للتَّفكير في حلِّ نشاطها. ----------------------------------------------------------- Résumé: Cette étude visait à révéler la réalité de la communication institutionnelle dans le secteur associatif, à partir de la réalisation d'une enquête sur un échantillon d'associations nationales actives au niveau de la Wilaya de Souk Ahras de l’Algérie. Dans son approche de la réalité, cette étude s'appuie sur une approche de base (marketing social dans le secteur associatif).Tous s'inscrivent dans le paradigme systémique qui considère l'institution (l'association) comme un système ouvert à son environnement interne et externe et à l'environnement général.Dans lequel les composants et les parties cherchent à atteindre l'objectif commun de la disposition générale dans le cadre d'un processus interactif pour réaliser les objectifs de la disposition en activant et en soutenant les efforts de communication afin d'aboutir à l'équilibre. Cette étude a abouti à un ensemble de résultats dont les plus importants sont résumés comme suit : - Premièrement - Concernant les éléments des processus de communication institutionnelle des associations étudiées: Les associations étudiées manquent de chargés de communications institutionnels qualifiés du fait de la grande rareté de formation ou de spécialisation dans ce domaine au niveau de certaines associations, et l'absence de celle-ci dans la majorité des associations.Ce qui a affecté négativement le reste des éléments du processus de communication en termes de mauvaise sélection des moyens et accessoires de communication.Une planification faible pour la formulation et le timing des messages de diffusion, ainsi qu'un manque de compréhension des meilleures façons de communications avec les différents publics à cause de manque d'études liées aux publics et leurs attentes de l'association. - Deuxièmement - Concernant les objectifs de communication institutionnelle dans le secteur associatif dans les associations étudiées: La plupart des associations étudiées cherchent à présenter leur identité de l'association d’une manière routinière et spontanée qui n’est pas étudiées car elles manquent d'une vision et d'une mission claire.Cela a affaibli la confiance des publiques en eux et leur communication avec eux, ce qui a affecté la construction d'un stéréotype (négatif) à leur sujet et le fait qu'ils soient des associations occasionnelles pour atteindre des objectifs personnels pour leurs membres. - Troisième - Obstacles à la communication institutionnelle dans le secteur associatif dans les associations étudiées: Les obstacles de la communication institutionnelle dans le secteur associatif dans les associations étudiées diffèrent et sont nombreux. Parmi les obstacles organisationnels, notamment le manque de spécialistes et la multiplicité des tâches, ce qui provoque parfois un déséquilibre organisationnel.Ainsi que des obstacles financiers tels que le problème de financement et le manque de siège pour les associations, qui ont conduit certaines associations à réfléchir à la dissolution de leurs activités.
دراسة مسحية على الجمعيات الناشطة بولاية سوق اهراس